Association of Malnutrition Based on Body Mass Index with A Presence of Oral Disease - Meta Maulida Damayanti; Yuniarti; Caecielia Makaginsar; Siska Nia Irasanti (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2021)
Background: To maintain oral health, the body needs good nutrition. The relationship between nutritional status and oral health conditions is very complex, influenced by many factors, both internal and external. Inadequate nutrition can increase the risk of oral disease. Purpose: To analyze the association between malnutrition and oral diseases. Methods: This study used the cross-sectional analytic observational design. Data were collected from the Manarul Huda Islamic Boarding School in Bandung, which 38 participants were selected based on criteria. Body mass index perform to asses nutritional status, while oral disease was collected through form data. Analysis’s data using chi-square and SPSS 23 version. Results: Classification of body mass index the highest in undernutrition group (47.4%) and oral disease the highest for tooth staining (52.6%), there was no significant association between malnutrition and oral disease with p value >0.05. Conclusion: Early analysis of nutritional assessment reduced oral disease. Further assessment will be needed to determine the long-term oral health effect of malnutrition.